Tau depletion in human neurons mitigates Aβ-driven toxicity - Ng, B; Vowles, J; Bertherat, F; Abey, A; Kilfeather, P; Beccano-Kelly, D; Stefana, MI; O’Brien, DP; Bengoa-Vergniory, N; Carling, PJ; Todd, JA; Caffrey, TM; et al. (Springer Nature [academic journals on nature.com], 2024)
Alzheimer’s disease (AD) is an age-related neurodegenerative condition and the most common type of dementia, characterised by pathological accumulation of extracellular plaques and intracellular neurofibrillary tangles that mainly consist of amyloid-β (Aβ) and hyperphosphorylated tau aggregates, respectively. Previous studies in mouse models with a targeted knock-out of the microtubule-associated protein tau (Mapt) gene demonstrated that Aβ-driven toxicity is tau-dependent. However, human cellular models with chronic tau lowering remain unexplored. In this study, we generated stable tau-depleted human induced pluripotent stem cell (iPSC) isogenic panels from two healthy individuals using CRISPR-Cas9 technology. We then differentiated these iPSCs into cortical neurons in vitro in co-culture with primary rat cortical astrocytes before conducting electrophysiological and imaging experiments for a wide range of disease-relevant phenotypes. Both AD brain derived and recombinant Aβ were used in this study to elicit toxic responses from the iPSC-derived cortical neurons. We showed that tau depletion in human iPSC-derived cortical neurons caused considerable reductions in neuronal activity without affecting synaptic density. We also observed neurite outgrowth impairments in two of the tau-depleted lines used. Finally, tau depletion protected neurons from adverse effects by mitigating the impact of exogenous Aβ-induced hyperactivity, deficits in retrograde axonal transport of mitochondria, and neurodegeneration. Our study established stable human iPSC isogenic panels with chronic tau depletion from two healthy individuals. Cortical neurons derived from these iPSC lines showed that tau is essential in Aβ-driven hyperactivity, axonal transport deficits, and neurodegeneration, consistent with studies conducted in Mapt−/− mouse models. These findings highlight the protective effects of chronic tau lowering strategies in AD pathogenesis and reinforce the potential in clinical settings. The tau-depleted human iPSC models can now be applied at scale to investigate the involvement of tau in disease-relevant pathways and cell types.